Millennial cold–dry events during marine isotope stage 11a based on sedimentary records from the Heqing Basin and their global climatic dynamical responses - Guohui Liu; Xinwen Xu; Shenghui Wang; Lirong Hou; Yuqing Zhang; Liu Yang; Jingfang Zhang; Yuzhu Zhang; Hui Zhao; Chaofeng Fu; Xiaoke Qiang; Wen Liu; et al. (Global and Planetary Change, 2026)

The amino acid Ser223 acts as a key site for the binding of Thrips palmi α1 nicotinic acetylcholine receptor to neonicotinoid insecticides - Kun Zhang; Jianwen Chen; Huixiu Huang; Huiqi Wen; Jingfang Yang; Junjie Geng; Shaoying Wu (Pesticide Biochemistry and Physiology, 2025)

Carbon-confinement modulated interfacial water structure for accelerated dissociation kinetics towards hydrogen evolution - Fanpeng Cheng; Yue Yu; Yulu Wan; Dashuai Wang; Shangqing Chen; Jingfang Zhang; Huijuan Guo; Yang Xia; Yi Huang; Lijuan Shi; Liwei Cheng; Qun Yi (Chemical Engineering Journal, 2025)

Prevalence of Avian Influenza Viruses and Biomolecular Analysis of H9N2 Subtype in Live Poultry Markets from 2021 to 2023 in Changsha, China - Xian Zhang; Yutong Wang; Xiaoyu Li; Zheng Huang; Huiyuan Fu; Ruiqing Pei; Caiying Zhu; Yu Di; Shan Chen; Jingfang Chen; Mingzhong Xu; Xuewen Yang; et al. (Food and Environmental Virology, 2025)

Protective effect of astragaloside IV against zinc oxide nanoparticles induced human neuroblastoma SH-SY5Y cell death: a focus on mitochondrial quality control - Liwei Wang; Lu Zhang; Yang Yun; Tingting Liang; Chaoqun Yan; Zhuoya Mao; Jingfang Zhang; Baoshe Liu; Jian Zhang; Taigang Liang (Molecular and Cellular Biochemistry, 2025)

Adding non-crop plants enhances parasitoid fitness on potato plants, but not pest densities - Yusha Wang; Yongping Zhou; Ruwen Li; Ambreen Masqsood; Hongsong Chen; Zhenqiang Qin; Jingfang Yang; Jiali Zhang; Lin Jing; Huihua Tan; Zhongshi Zhou (Crop Protection, 2025)

Systematic engineering for high-level production of β-nicotinamide mononucleotide from NAM and ribose - Tianqi Bao; Pingping Weng; Jingfang Wang; Shumei Cui; Yong Tao; Jianzhong Huang; Xinwei Yang; Chongrong Ke (Food Bioscience, 2025)

Co-pyrolytic drivers and volatiles of 3D printing waste and textile dyeing sludge and their multi-objective optimization - Ziting Lin; Xiaoming Li; Jingfang Mou; Fatih Evrendilek; Jingyong Liu; Jiayu Liang; Sen Lin; Haiming Cai; Yao He; Guanzheng Zhuang; Chunxiao Yang (Chemical Engineering Journal, 2024)

A two-photon fluorescent probe for highly selective detection of Cys over GSH and Hcy based on the Michael addition and transcyclization mechanism and its application in bioimaging and protein straining in SDS-PAGE - Qi Sun; Ting Zhang; Yuchen Ren; Yuan Qiu; Xiaogang Luo; Jingfang Yang; Genyan Liu (Analytica Chimica Acta, 2024)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

PBX1-promoted SFRP4 transcription inhibits cell proliferation and epithelial-mesenchymal transition in endometrial carcinoma - Liwen Guo; Huihua Chen; Jinguo Chen; Chen Gao; Xianguo Fu; Sujuan Zhou; Wenjuan Wu; Taoping Li; Jingfang Lin; Tailai Yang; Zichun Chen; Luoyuan Cao (Tissue and Cell, 2023)

Effects of nitrogen and phosphorus supply levels and ratios on soil microbial diversity-ecosystem multifunctionality relationships in a coastal nontidal wetland - Kai Sun; Jingfang Cai; Xiaoling Liu; Lijuan Yang; Hongli Li; Guangmei Wang; Xingliang Xu; Feihai Yu (Science of The Total Environment, 2023)

Evaluation of novel isolates of Lacticaseibacillus rhamnosus Probio-M9 derived through space mutagenesis - Jingfang Yang; Yue Sun; Xueyan Lei; Lixia Zhao; Rui Luo; Wenjun Liu (Food Bioscience, 2023)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

Increased greenhouse gas emissions intensity of major croplands in China: Implications for food security and climate change mitigation - Jingting Zhang; Hanqin Tian; Hao Shi; Jingfang Zhang; Xiaoke Wang; Shufen Pan; Jia Yang (Global Change Biology, 2020)
Balancing crop production and greenhouse gas (GHG) emissions from agriculture soil requires a better understanding and quantification of crop GHG emissions intensity, a measure of GHG emissions per unit crop production. Here we conduct a state‐of‐the‐art estimate of the spatial‐temporal variability of GHG emissions intensities for wheat, maize, and rice in China from 1949 to 2012 using an improved agricultural ecosystem model (Dynamic Land Ecosystem Model‐Agriculture Version 2.0) and meta‐analysis covering 172 field‐GHG emissions experiments. The results show that the GHG emissions intensities of these croplands from 1949 to 2012, on average, were 0.10–1.31 kg CO 2 ‐eq/kg, with a significant increase rate of 1.84–3.58 × 10 –3 kg CO 2 ‐eq kg −1 year −1 . Nitrogen fertilizer was the dominant factor contributing to the increase in GHG emissions intensity in northern China and increased its impact in southern China in the 2000s. Increasing GHG emissions intensity implies that excessive fertilizer failed to markedly stimulate crop yield increase in China but still exacerbated soil GHG emissions. This study found that overfertilization of more than 60% was mainly located in the winter wheat–summer maize rotation systems in the North China Plain, the winter wheat–rice rotation systems in the middle and lower reaches of the Yangtze River and southwest China, and most of the double rice systems in the South. Our simulations suggest that roughly a one‐third reduction in the current N fertilizer application level over these “overfertilization” regions would not significantly influence crop yield but decrease soil GHG emissions by 29.60%–32.50% and GHG emissions intensity by 0.13–0.25 kg CO 2 ‐eq/kg. This reduction is about 29% and 5% of total agricultural soil GHG emissions in China and the world, respectively. This study suggests that improving nitrogen use efficiency would be an effective strategy to mitigate GHG emissions and sustain China's food security.

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Computational Study of HCV p7 Channel: Insight into a New Strategy for HCV Inhibitor Design - Beili Ying; Shichao Pang; Junchen Yang; Yang Zhong; Jingfang Wang (Interdisciplinary Sciences: Computational Life Sciences, 2019)

NAC transcription factor ONAC066 positively regulates disease resistance by suppressing the ABA signaling pathway in rice - Qing Liu; Shijuan Yan; Wenjie Huang; Jianyuan Yang; Jingfang Dong; Shaohong Zhang; Junliang Zhao; Tifeng Yang; Xingxue Mao; Xiaoyuan Zhu; Bin Liu (Plant Molecular Biology, 2018)

Characterization and genomic analyses of Aeromonas hydrophila phages AhSzq-1 and AhSzw-1, isolates representing new species within the T5virus genus - Shengjian Yuan; Ling Chen; Quan Liu; Yan Zhou; Jingfang Yang; Deng Deng; Hongping Li; Yingfei Ma (Archives of Virology, 2018)

Proper balance of omega-3 and omega-6 fatty acid supplements with topical cyclosporine attenuated contact lens-related dry eye syndrome - Ling Wang; Xi Chen; Jingfang Hao; Lu Yang (Inflammopharmacology, 2016)

The germin-like protein OsGLP2-1 enhances resistance to fungal blast and bacterial blight in rice - Qing Liu; Jianyuan Yang; Shijuan Yan; Shaohong Zhang; Junliang Zhao; Wenjuan Wang; Tifeng Yang; Xiaofei Wang; Xingxue Mao; Jingfang Dong; Xiaoyuan Zhu; Bin Liu (Plant Molecular Biology, 2016)

MicroRNA-135b regulates metastasis suppressor 1 expression and promotes migration and invasion in colorectal cancer - Weiyun Wu; Zhuang Wang; Pengchun Yang; Jingfang Yang; Jian Liang; Yuanhong Chen; Hao Wang; Guoli Wei; Shicai Ye; Yu Zhou (Molecular and Cellular Biochemistry, 2014)